/ Pengaruh Proporsi Ketan Putih dan Daunxkelork(Moringapoleifera Lamk.)PterhadapkSifatjFisikkMasker Bubuk Tradisional - Setyorini, Pipit; Suhartiningsih, Suhartiningsih (Journal of Beauty and Cosmetology (JBC), 2020)
A traditional powder mask is a mask with a powder texture made from natural ingredients. This study uses natural ingredients of white sticky rice and active ingredients moringa leaves and aromatic ingredients of kaffir lime peel is used to minimize the unpleasant scent of moringa leaves. This type of research is experimental. The independent variable of this study is the proportion of white sticky rice flour and moringa leaf powder which are X1(4:3), X2 (5:2), X3 (6:1). Dependent variables are physical properties which include color, scent, texture, stickiness, and panelist preference level. Data collection using the method of observation conducted by 35 panelists. Data analysis used single way analysis (one-way ANOVA) and Duncan test with the help of SPSS version 16. Based on Duncan's test results the best results are shown in X3 with colored criteria greenish-white, moderately scented with moringa leaves, and moderately scented with kaffir lime peel, textured quite smooth, quite sticky, and most preferably panelist. Based on the results of microbiological tests mask of white sticky flour and moringa leaf powder can be seen that has the number of bacteria and fungi detected below the maximum limit of 10âµ. Mask of white sticky flour and moringa leaf powder products can be used until the 7th day and according to Decree of the Director-General of Drug and Food Control Ministry of  Health of the Republic Indonesia Number: HK.00.06.4.02894.Keywords: Traditional powder mask, white sticky rice, moringa leaf, kaffir lime peel